Cost Of Production Analysis and Break Event Point of Crude Palm Oil Production On PT. Sandabi Indah Lestari - Ika Ariyanti; Bambang Sumantri; Sriyoto Sriyoto; Eko Sumartono (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2018)
To determine the exact cost of production, the compony must take into account precisely the elements of the production cost. Elements of the production cost on the research is raw material cost, direct labor cost, and manufacture overhead cost. Break event point analysis relate to sale, fixed cost, and variable cost. All of these cost are costs associated with the production process of Crude Palm Oil. Make, this research count the cost of production and break event point Crude Palm Oil PT. Sandabi Indah Lestari (PT. SIL) from 2009-2014.This research uses design research of descriptive analysis and quantitaive analysis. Cost of production CPO to use method of full costing because used data represent and have passed accounting period. Cost of production and break event point of the research analysed in 2 form that is on the basis of rupiah and on the basis unit. Result of research indicate that sales revenue of CPO more than cost of production and break event point in rupiah and also in unit. Matter this means that company have obtained profit of production.